# SOLUTION: CAN SOMEONE HELP ME WITH THIS PROBLEM Solve the eqation for s. log(9s-7)=r-2 10^(r-2)=9s-7 10^(r-2)+7=9s-7+7 10^(r-2)+7=9s (10^(r-2)+7)/9=9s/9 (10^(r-2))/9 + 7/9 =s

Algebra ->  Algebra  -> Polynomials-and-rational-expressions -> SOLUTION: CAN SOMEONE HELP ME WITH THIS PROBLEM Solve the eqation for s. log(9s-7)=r-2 10^(r-2)=9s-7 10^(r-2)+7=9s-7+7 10^(r-2)+7=9s (10^(r-2)+7)/9=9s/9 (10^(r-2))/9 + 7/9 =s       Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Polynomials, rational expressions and equations Solvers Lessons Answers archive Quiz In Depth

 Question 162055: CAN SOMEONE HELP ME WITH THIS PROBLEM Solve the eqation for s. log(9s-7)=r-2 10^(r-2)=9s-7 10^(r-2)+7=9s-7+7 10^(r-2)+7=9s (10^(r-2)+7)/9=9s/9 (10^(r-2))/9 + 7/9 =s Found 2 solutions by tutor_paul, eperette:Answer by tutor_paul(490)   (Show Source): You can put this solution on YOUR website!Solve for s: ==================== First, take the anti-log of both sides of the equation. That means making each side of the equation the exponent of 10: Use a log property to rewrite the left side of the equation: Solve for s: ===================== Good Luck, tutor_paul@yahoo.com Answer by eperette(173)   (Show Source):